THE EFFECT OF THINK PAIR SHARE MODEL USING VIDEO SCRIBE MEDIA ON COMMUNICATION SKILLS AND MOTIVATION TO LEARN IPS - Agustin, Eka; Nawir, Muhammad; Kaharuddin, Kaharuddin (Conciencia, 2023)
The purpose of this study was to determine the effect of Think Pair Share (TPS) learning model using Video Scribe on communication skills and motivation to learn social studies of fifth grade students of SD Inpres Tappanjeng Bantaeng Regency. This type of research is quantitative using an experimental approach. The research design used was Nonequivalent Control Group Design. The population in this study were 36 students. The samples in this study were class VA with 18 students as the experimental class and class VB with 18 students as the control class. The sampling technique used saturated sampling. The instruments used were observation sheets and questionnaires. Data collection techniques in this study were observation, questionnaire and documentation. The data analysis techniques used were descriptive data analysis and inferential statistical analysis. The hypothesis tests used were Anova and Manova. The results obtained are the significance value of communication skills and motivation to learn social studies students smaller than 0.05 which means H1 is accepted and H0 is rejected, namely there is an effect of Think Pair Share learning model using Video Write Communication Skills and Motivation to Learn Social Studies Students Grade V Elementary School.